Equity, Equality, and Educational Inspectorate. From Data to Equity and Equality - Ituarte Pérez, Maider; Casado Goti, Martín (Avances en Supervisión Educativa, 2025)
This article is based on a paper presented at the XVII State Congress of ADIDE Federation held in Cordoba in November 2024, under the title: ‘Equity, Equality and Educational Inspection’. The paper was entitled: ‘From data to equity and equality’. The contents were focused on data from external evaluations (Diagnostic Evaluation and International Evaluations), as well as research data: what educational and organisational practices are considered effective. It is important to note that each of the above points in turn developed along two axes. The first axis, the reading of data: What kind of data does a school and its inspector know, and does it really reflect what is happening in the classroom, is it reliable, and what is the origin and purpose of the data collector? The second axis, actions: What can be done with these data? How can they be interpreted? How useful are they for teaching, organisational, and inspection work? How can they be managed to improve teaching and learning processes, so that students can better develop their competences, their citizenship, and their fulfilment?